Big Five Personality Terhadap Perilaku Phubbing Pada Siswa SMA - Novita Suhendriani; Sigit Nugroho (UIR Press, 2022)
The times have progressed in various aspects of life, one of which is the development of smartphones important aspect. The positive benefits of using a smartphone make it an important object. However, the impact caused by excessive smartphone use will reduce empathy and sympathy for other people and the environment. Ignoring the interlocutor because he is complacent when using access on a smartphone is called phubbing behavior. The purpose of this study was to determine the influence of the five big five personality traits, namely extraversion, agreeableness, conscientiousness, emotional stability, and intellect on phubbing behavior experienced by adolescents at the 14 Pekanbaru State Senior High School (SMAN) level. The data collection method used the IPIP-BFM-25 big five personality scale and the phubbing behavior scale. A total of 250 students of SMAN 14 Pekanbaru were sampled in this study. The sampling technique used is a non-probability sampling technique with purposive sampling method. The results of the analysis show that there is a significant influence in a negative direction between the big five personalities on phubbing behavior in students at SMAN 14 Pekanbaru. Of the five big five personality traits, there are two traits, namely conscientiousness and intellect which influence phubbing behavior.